2010
DOI: 10.1093/eurheartj/ehq400
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin-1 plasma levels are associated with the severity of hypertrophy in hypertrophic cardiomyopathy

Abstract: AimsCardiotrophin-1 (CT-1) is a cytokine that induces hypertrophy in cardiomyocytes and is associated with left ventricular hypertrophy (LVH) in hypertensive patients. The objective of this study was to evaluate whether plasma CT-1 is associated with hypertrophic cardiomyopathy (HCM).Methods and resultsThe study was performed in 124 patients with HCM. All patients underwent a full clinical evaluation and an echocardiogram. Left ventricular hypertrophy was evaluated by the measurement of the maximal LV wall thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
21
0
2
Order By: Relevance
“…Some patients from this cohort are reported in other recently published studies 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25…”
Section: Methodsmentioning
confidence: 88%
“…Some patients from this cohort are reported in other recently published studies 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25…”
Section: Methodsmentioning
confidence: 88%
“…In humans, elevated serum levels of CT-1 have been observed in patients with heart failure (HF) [33] and hypertensive heart disease [34]. While some authors have reported an association between circulating CT-1 and left ventricular structure and function [34][35][36][37][38][39], other studies could not confirm these findings [40]. Elevated CT-1 mRNA and protein were observed in the ventricles from rats with myocardial infarction, and in patients with ischemic heart disease, valvular heart disease or after myocardial infarction (MI) [41].…”
Section: Cardiovascularmentioning
confidence: 99%
“…Interestingly, treatment-induced decrease of plasma cardiotrophin-1 paralleled LV hypertrophy regression in treated hypertension [19,25]. Data also support an association between cardiotrophin-1 and LV mass in other pathologic states, including hypertrophic [27] and dilated cardiomyopathy [28]. Other authors could not confirm, however, the above findings.…”
mentioning
confidence: 89%
“…Second, the limited sample size and the tiny number of normotensive controls (only 25 patients) make it difficult to draw definite conclusions on the independent contribution of cardiotrophin-1 in stratifying the risk of LV systolic dysfunction. Third, most of the published studies on the association between circulating cardiotrophin-1 and LV structure and function have been obtained by the same research group [19][20][21][22][24][25][26][27]30], whereas studies from other groups could not confirm the same findings [29]. Also, the inclusion of hypertensive patients under blood pressure-lowering drug treatment may be misleading in the interpretation of the study results.…”
mentioning
confidence: 98%